If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8 = 5 + -1(9 + -1b) -8 = 5 + (9 * -1 + -1b * -1) -8 = 5 + (-9 + 1b) Combine like terms: 5 + -9 = -4 -8 = -4 + 1b Solving -8 = -4 + 1b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-1b' to each side of the equation. -8 + -1b = -4 + 1b + -1b Combine like terms: 1b + -1b = 0 -8 + -1b = -4 + 0 -8 + -1b = -4 Add '8' to each side of the equation. -8 + 8 + -1b = -4 + 8 Combine like terms: -8 + 8 = 0 0 + -1b = -4 + 8 -1b = -4 + 8 Combine like terms: -4 + 8 = 4 -1b = 4 Divide each side by '-1'. b = -4 Simplifying b = -4
| 3t^2+43t+14=0 | | 15(a^2)b+22ab+8b=0 | | 4m+8n-6q=0 | | 18=7-(a+10) | | 13x^2-24x-288=0 | | 8m^2+44m+60=0 | | 9(2h+7)+3w= | | k/3=1.5 | | 1/3(8-x)=8-x/2 | | 288=72(h) | | 1/2lnx=-1 | | (2t+7)+6=73 | | 6.28*3/2*13/6x | | 1/2(3j) | | 0.210=3735x-0.006588 | | -(1/3)^1 | | 9t^2-48t+39=0 | | 10n+14=74 | | 3x^2+4x-mn=0 | | .35x=36 | | 5v^2+44v-9=0 | | 3x^2+4x-m*n=0 | | 5v+44v-9=0 | | Ln(x)+ln(x+7)=5 | | Ln(x)-ln(x+7)=5 | | 9h-12h=54-13 | | x+(x)(2)+x-3=39 | | 3w^2+11w+6=0 | | P=0.5q+0.5 | | 4=×/14 | | 3g^2-14g+16=0 | | -54=6k |